Cation‐π Interaction‐Mediated Tumour Drug Delivery for Deep Intratumoral Penetration and Treatment. (30th July 2022) - Liu, Chengfei; Li, Muqiong; Sun, Jianxiang; Li, Pengxiang; Bai, Yang; Zhang, JuAn; Qian, Yongchao; Shi, Menghan; He, Jia; Huo, Hongbin; Pang, Jun; Fan, Li; et al.
Abstract: The limited efficacy of deep tumor treatments has been considered the "Achilles' heel" of anticancer therapy due to multiple biological barriers. Whether passive diffusion or active transport has difficulties completely overcoming these obstacles. Herein, cation‐π interactions are utilized to construct a tumor drug delivery system integrating the merits of both passive and active transport mechanisms. A cation‐π interaction bridged trimetallic supramolecular drug complex (Cπ‐TMSDC ) is constructed based on a drug consisting of one cisplatin molecule linked by K + (Pt‐COOK ) and the other drug with a Ru metal complex containing curcumin (Ru‐Cur ). The obtained Cπ‐TMSDC further self‐assembles into cation‐π‐based trimetallic supramolecular drug micelles (Cπ‐TMSDMs ) with efficient and stable transportation in vivo due to the strong cation‐π interaction formed between K + and the curcumin unit in the Cπ‐TMSDC . In acidic tumor microenvironment, the cation‐π interaction smartly dissociates, facilitating the quick release of Pt‐COOK outside Cπ‐TMSDMs to rapidly infiltrate the outer cellular layers by passive diffusion. Meanwhile, the dissociated Ru‐Cur from the core layer of the Cπ‐TMSDMs form secondary self‐assemblies to deeply penetrate inside the solid tumor. Therefore, this strategy results in an efficient tumor drug delivery platform with enhanced deep intratumoral penetration, improved therapeutic effects, and reduced systemic toxicity to normal organs. Abstract : A cation‐π interaction bridged trimetallic supramolecular drug complex (Cπ‐TMSDC ) is first designed, which integrates the merits of both passive and active transport mechanisms, achieving rapid infiltration into the outer cellular layers by passive diffusion and realizing long‐lasting treatment in the inner layers of solid tumors through active transport to obtain a sufficient amount of drug in deep tumors.